GENETIC POLYMORPHISM AND DIVERSITY OF IRAQI AWASSI SHEEP USING PCR-RAPD TECHNIQUE - Zainab S. Al-Allak; Maytham A. Dragh; Ahmed Sadoon Hussain (Basrah Journal of Veterinary Research)
The establishment of modern sheep production systems in Iraq, lead to presence of variousforms of hybridization between the native and Middle East breeds which have been utilized forgenetic improvement. This occur in consistence with the progressive destruction or deteriorationof sheep habitat. Together, these factors have accelerated the loss of genetic diversity or evenresulted in the extinction of some indigenous breeds. Therefore, it is important to developefficient strategies for surveillance, evaluation, conservation and utilization of the availablegenetic resources for this species. Seven random amplification polymorphism DNA (RAPD)marker used. The aim of this study was to assess genetic diversity for Awassi native breed inIraq. The higher polymorphism information contents at the seven markers (Seventy- three bandsobtained with 28.3% of polymorphism) indicate the retention of natural variation from sourcepopulations for the domestic breeds of different geographic regions in Iraq. Analysis of geneticdifferentiation revealed substantial divergence among these breeds as 16% diversity indicatingthat some evolutionary forces (e.g. selection and migration, uncontrolled selling across borders)had acted on these populations. Phylogenetic and phylogeographic analyses displayed aremarkable degree of consistency between geographic origins, breeding histories and the patternof genetic differentiation.